"Nada levarei quando morrer, aqueles que mim deve cobrarei no inferno" ("Nothing I will take when I die those who owe me mony I will charge in hell"), a film by Miguel Rio Branco - Klautau Filho, Mariano (PORTO ARTE: Revista de Artes Visuais, 2017)
"Nada levarei quando morrer, aqueles que mim deve cobrarei no inferno" ("Nothing I will take when I die those who owe me mony I will charge in hell"), produced by Miguel Rio Branco in 1981 and captured in 16mm film in 1979 is a raid on the Community of Maciel, prostitution district in the neighborhood of Pelourinho in Salvador, Bahia. The street, the brothels, the architecture in ruins and, in particular, women and their scars make up a human landscape of social and erotic tension. The film is the document of a lived experience of brazilian reality and an exercise on the picture, the body and the pose. The moving image converses with still images, noises and music building a space of approximation and confrontation with the place in which the dynamic between photo and cinema is the poetry of the artist and his experience in the Decade of 1980.